Un signo léxico de demarcación en griego antiguo - Him Fábrega, Rodrigo (Universidad Nacional de La Plata. Facultad de Humanidades y Ciencias de la Educación. Centro de Estudios Helénicos, 2015)
The analysis shows that the Greek verb Ï†Î·Î¼Î¯ is a marker of change of phase in the dialogue incorporated to the narrative sequence of a sample of texts from the classical period, behaving as a sign of boundary in such level of the language structure